The Steroid Receptor Coactivator-3 Is Required for the Development of Castration-resistant Prostate Cancer - Tien, Jean Ching-Yi (2013)
The transcriptional coactivator SRC-3 plays a key role to enhance prostate cancer (CaP) cell proliferation. Although SRC-3 is highly expressed in advanced CaP, its role in castration resistant CaP (CRPC) driven by PTEN mutation is unknown. We documented elevated SRC-3 in human CRPC and in PTEN-negative human CaP. Patients with high SRC-3 and undetectable PTEN exhibited decreased recurrence-free survival. To explore the causal relationship in these observations, we generated mice in which both Pten and SRC-3 were inactivated in prostate epithelial cells (Pten3CKO mice), comparing them to mice in which only Pten was inactivated in these cells (PtenCKO mice). SRC-3 deletion impaired cellular proliferation and reduced tumor size. Notably, while castration of PtenCKO control mice increased the aggressiveness of prostate tumors relative to non-castrated counterparts, deletion of SRC-3 in Pten3CKO mice reversed all these changes. In support of this finding, castrated Pten3CKO mice also exhibited decreased levels of phospho-Akt, S6 kinase (RPS6KB1) and phosphorylated S6 protein (RPS6), all of which mediate cell growth and proliferation. Moreover, these tumors appeared to be more differentiated as evidenced by higher levels of Fkbp5, an AR-responsive gene that inhibits Akt signaling. Lastly, these tumors also displayed lower levels of certain androgen-repressed genes such as cyclin E2 and MMP10. Together, our results show that SRC-3 drives CRPC formation and offer preclinical proof of concept for a transcriptional coactivator as a therapeutic target to abrogate CRPC progression.